A Persistent Depletion of Plasma Ions Within Jupiter's Auroral Polar Caps. Issue 23 (1st December 2020) - Pollock, C. J.; Ebert, R. W.; Allegrini, F.; Bagenal, F.; McComas, D. J.; Szalay, J. R.; Valek, P.
Abstract: Regions poleward of Jupiter's main auroral ovals are largely devoid of 0.01 to 46 keV/q ions. We report ion measurements from the plasma instrument on the Juno spacecraft in polar orbit around Jupiter that characterize the presence or absence of structured ion fluxes poleward of the main ovals. We approximate geometric centers of published north and south Jovian main ovals and develop a probability metric for observation of plasma ions as a function of angular distance from these centers to the magnetic foot points of the observations, in the north and south separately. Using data from Juno's first 26 perijoves, at Jovicentric distances of 1.06 to 12 RJ, this metric shows a systematic decrease within both north and south main ovals, in the probability of observing plasma ions as the chosen centers are approached. This is consistent with previous reports of large electrostatic potential drops above Jupiter's polar caps. Plain Language Summary: Statistical analysis of ion fluxes above Jupiter's polar caps at Jovicentric distances ranging from less than 1.1 to nearly 12 planetary radii demonstrates a systematic absence of energy‐structured ions in the studied energy range. This, combined with previous case studies of Juno energetic particle measurements in the same regions, means that plasma ions from the dense ionosphere below are likely excluded from the midaltitude regions by electrostatic potential barriers. Exclusion of plasma ions from higher altitudes may indicate a lack of outer magnetosphere source ions or exclusion of any source ions by a complex magnetic field geometry induced by the fast planetary rotation. This work provides a further example of profound differences between the Jovian and Terrestrial magnetosphere systems. Key Points: Ion at energies per charge between 10 V and 46 kV is persistently depleted within the Jovian auroral polar caps Probability of observing such fluxes increases with increasing distance from the centers of the statistical north and south main ovals Absence of ion plasma is consistent with formation of large downward E fields above the Jovian polar caps as previously reported